STUDI DESKRIPTIF PEMBERIAN PHYSICAL THERAPY EXERCISE PADA KONDISI NYERI PUNGGUNG BAWAH MYOGENIC: STUDI DESKRIPTIF PEMBERIAN PHYSICAL THERAPY EXERCISE PADA KONDISI NYERI PUNGGUNG BAWAH MYOGENIC - Arief, Hendrawan; Engkartini, Engkartini; Setiyawati, Dwi (Jurnal Kesehatan Al-Irsyad, 2021)
Back pain is a musculoskeletal pain that is often expressed by clients. Back pain varies widely. Pain can be ordinary, stabbing and can even be radiating. One type of back pain is myogenic lower back pain. Myogenic lower back pain is a type of back pain caused by disturbance in the musculoskeletal system in the thoracal thoracic area 12 to the area around the buttocks without any neurological problems. Physiotherapy plays a role in the management of low back pain. Physiotherapy measure given can be in the form of modality therapy or exercise therapy. Exercise therapy given to low back pain conditions varies depending on the physical disorder complained of by the client/patient. This study aims to provide an overview of the provision of exercise therapy in conditions of myogenic low back pain. The research method is descriptive analytic. This study was followed by 40 respondents who are physiotherapists in the Cilacap-Banyumas-Purbalingga area. The research time was from March to November 2020. The research instrument used a questionnaire. The result showed a description of the provision of exercise therapy in conditions of myogenic low back pain.